A Comparative Study of the effect of aqueous extract of Vitex agnus-castus plant on male and female’s liver’s enzymes of mice exposed to oxidative stress - Muneef Saab- Ahmed Al-Janabi; Usmat Jamal Jamel; Zeyad Tariq Ahmed Al-Duri (Tikrit Journal of Pure Science, 2023)
This study was conducted to determine the Protective effect of aqueous extracts of Vitex agnus castus plant both doses, Normal active does(50mg/kg) and double (100mg/kg) in the liver enzymes and comported the deferent effect of it between the male and female’s of Mice, that exposed to oxidative stress induced by hydrogen peroxide (0.5%) with drinking water for (30) days, there were distributed into 10 groups which are (control group, H2O2 group, active dose of aqueous extracts of Vitex group,  active dose of aqueous extracts of Vitex + H2O2, active dose of aqueous extracts of Vitex + H2O2 + vitamin E, active dose of aqueous extracts of Vitex+ vitamin E, double dose of aqueous extracts of Vitex, double dose of aqueous extracts of Vitex+H2O2, double dose of aqueous extracts of Vitex+H2O2+vitamin E, vitamin E + H2O2 .